Isolation and structure elucidation of the major individual polyphenols in carob fibre - Owen, Robert; Haubner, R.; Hull, William Edmund; Erben, G.; Spiegelhalder, Bertold; Bartsch, Helmut; Haber, B. (Food and chemical toxicology, 2003)
Although it is already known that carob fibre contains several classes of polyphenolic substances, a comprehensive analysis of these has not been conducted to date. Therefore, the major polyphenolic compounds were extracted with organic solvents, and, following fractionation by normal-phase column chromatography on silicic acid, their structures were elucidated by liquid-chromatography electrospray-ionisation mass spectrometry (LC-ESI), nano-electrospray-ionisation mass spectrometry (ESI-MS), and gas-chromatography mass spectrometry (GC-MS). In addition, complete 1H and 13C NMR assignments were obtained for the isolated gallotannins 1,6-di-, 1,2,6-tri- and 1,2,3,6-tetra-O-galloyl-β-d-glucose. Carob fibre was found to contain a rich variety of phenolic antioxidants. A total of 24 polyphenol compounds were identified with a yield of 3.94 g/kg (dry weight). The profile was dominated by gallic acid in various forms: free gallic acid (42% of polyphenols by weight), gallotannins (29%), and methyl gallate (1%), while simple phenols, mainly cinnamic acid, made up about 2% of the total. Flavonoids represented 26% of the polyphenols, and the major components were identified as the glycosides myricetin- and quercetin-3-O-α-l-rhamnoside (ca. 9% and 10%, respectively). These data indicate that carob fibre is rich in both amount and variety of phenolic antioxidant substances, and its inclusion in the diet may have chemopreventive properties.
Gesehen am 23.11.2020